2018
DOI: 10.1159/000490874
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Tumor DNA as a Sensitive Marker in Patients Undergoing Irreversible Electroporation for Pancreatic Cancer

Abstract: Background/Aims: Pancreatic ductal adenocarcinoma (PDAC) is often diagnosed at an advanced stage, resulting in extremely poor 5-year survival. Late diagnosis of PDAC is mainly due to lack of a reliable method of early detection. Carbohydrate antigen (CA) 19-9 is often used as a tumor biomarker in PDAC; however, the test lacks sensitivity and specificity. Therefore, new sensitive and minimally invasive diagnostic tools are required to detect pancreatic cancer. Methods: Here, we investigated circulating tumor DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…In relation to technical aspects, previous studies have interrogated regions ranging from a single locus of KRAS to comprehensive cancer panels covering >20 genes. 9,30,35,37 PDAC shows a very homogeneous mutational landscape with KRAS mutations in approximately 90% of cases, barring the need for extensive coverage and patient-tailored primers. 18,38,39 This implies that ddPCR, which has a lower limit of detection than NGS, would be eminently suited to PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to technical aspects, previous studies have interrogated regions ranging from a single locus of KRAS to comprehensive cancer panels covering >20 genes. 9,30,35,37 PDAC shows a very homogeneous mutational landscape with KRAS mutations in approximately 90% of cases, barring the need for extensive coverage and patient-tailored primers. 18,38,39 This implies that ddPCR, which has a lower limit of detection than NGS, would be eminently suited to PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in‐depth studies of the pathogenesis of CRC play an important role in human health. Liu et al demonstrated that underexpressed miR‐124 could regulate inhibitor of apoptosis‐stimulating protein of p53 (iASPP) in CRC patients and was related to the proliferation of CRC cells via influencing the iASPP/NF‐kB pathway . In addition, miR‐124 inhibited the target gene polypyrimidine tract‐binding protein 1 (PTB1) in the DLD‐1 CRC cell line.…”
Section: Mir‐124 and Colorectal Cancermentioning
confidence: 99%
“…Pancreatic cancer is always diagnosed in late stage due to the lack of clinical manifestations. 60 So far, there are not many effective targeted therapies to reduce its mortality. 61 Emphasis has been placed on deeply investigating miR-124 to reveal its role as a tumor suppressor or protooncogene.…”
Section: Mir-124 and Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, KRAS mutant ctDNA represents a promising biomarker and therapeutic target of PC. Using ddPCR and targeted NGS, different KRAS mutations were detected in up to 80% of PC serum and plasma samples and were associated with decreased survival (Adamo et al 2017;Ako et al 2017;Chen et al 2010;Cohen et al 2017;Dabritz et al 2009;Del Re et al 2017;Dianxu et al 2002;Earl et al 2015;Hadano et al 2016;Jiao et al 2007;Kim et al 2018;Kinugasa et al 2015;Kruger et al 2018;Lin et al 2018;Maire et al 2002;Marchese et al 2006;Nakano et al 2018;Park et al 2018;Patel et al 2019;Perets et al 2018;Pratt et al 2019;Riviere et al 2018;Sausen et al 2015;Semrad et al 2015;Sugimori et al 2020;Takai et al 2015;Tjensvoll et al 2016;Uemura et al 2004;Van Laethem et al 2017;Watanabe et al 2019;Wu et al 2014). Chen et al published a KRAS mutant ctDNA detection rate of 93.7% which correlates with time to progression and overall survival of 189 patients with unresectable PC (Chen et al 2017).…”
Section: Genomic Alterations Of Ctdna In Pcmentioning
confidence: 99%